Environmental diagnosis and application of the risk analysis of a tributary of the Poxim River, Sergipe-Brazil (Research, Society and Development, 2020)
The land use and occupation in the Poxim river hydrographic sub-basin, in Sergipe, affects the condition of its water quality due to the intense urbanization process in the region. Factors such as disordered population growth, housing built on the banks of the beds, deforestation and the lack of adequate sewage services have led to degradation of this source. The risk analysis is a calculation method that assesses the changes caused by the various anthropogenic activities to a specified system through the integration of variables represented within lines of evidence, thus allowing the risk to be valued for one ecosystem. In this context, the objective of this work was to evaluate the degree of degradation, to identify possible factors of water contamination and to analyze the risk existing in a tributary of the Poxim river in São Cristóvão, Sergipe. For the application of the methodology, three sampling points of this tributary were defined in addition to the use of values from CONAMA Resolution nº 357/2005 as the normative reference. The results obtained showed that the alterations identified are related to the anthropic uses that occur along the stream. The chemical evidence line, which varied between low and medium risk, and the ecological line, estimated to be of very high risk, were valued. With the integration of the lines, the risk value ranged from high to very high, meaning that the hydrographic sub-basin needs emergency recovery measures.